Liposome encapsulated perfluorohexane enhances radiotherapy in mice without additional oxygen supply. Issue 1 (December 2016) - Xu, Linfeng; Qiu, Xuefeng; Zhang, Yanting; Cao, Kai; Zhao, Xiaozhi; Wu, Jinhui; Hu, Yiqiao; Guo, Hongqian
Abstract Background To investigate the effect of perfluorochemical preparations in enhancing radiotherapy, perfluocarbon nanoparticles were by encapsulating perfluorohexane into liposome [lip(PFH)]. Methods After intravenous injection, lip(PFH) could accumulate in the tumor site over time, with a prominent accumulation in tumor 24 h post injection. X-ray was delivered to the tumor site 24 h after the injection of lip(PFH) under room air. The experimental mice were randomized into four groups: control (saline), lip(PFH) (lip(PFH) only), X-ray (X-ray only), and lip(PFH) + X-ray (lip(PFH) with X-ray radiation). Tumor volume and histology were monitored to assess treatment efficacy. Results Tumor growth was significantly reduced in mice received lip(PFH) and X-ray compared with X-ray only. The histological data also revealed more destruction of tumor tissue in lip(PFH) + X-ray group compared with X-ray only. In addition, lip(PFH) did not show any significant tissue damage to major organs or induce significant liver/kidney dysfunction. Conclusions Lip(PFH) could accumulate in the tumor site and enhance radiotherapy without additional oxygen supply.